Laser printing of conductive tracks with extremely low electrical resistance on polymer–carbon nanotubes composite: An optimization study of laser setup parameters by design of experiment approach. Issue 9 (4th November 2017) - Caradonna, Andrea; Tagliafierro, Francesca; Veca, Antonino; Badini, Claudio
Abstract : Metal‐free conductive tracks were obtained on polycarbonate/acrylonitrile–butadiene–styrene (PC/ABS)‐multiwall carbon nanotube (MWCNT) nanocomposites by laser printing technology. Laser printing is a novel technique able to promote polymer pyrolysis leading to the formation of conductive tracks embedded on the surface of polymer‐based nanocomposites. The resulting material is characterized by the presence of different not interactive conductive pathways. The aim of this article is to analyze the effect of the laser parameters setup on the electrical resistivity of laser printed tracks. To have a complete comprehension of the process, a design of experiment (DOE) approach was used. By analyzing the experimental outcomes with a statistical approach, it was possible to focus the attention on the main laser parameters that govern the process, thus obtaining multifunctional and multidirectional conductive materials with surface electrical resistance per length unit (inside the tracks) lower than 1 kΩ/cm at 0.5 wt% of MWCNT loading content. POLYM. ENG. SCI., 58:1485–1493, 2018. © 2017 Society of Plastics Engineers